Psychometric evidence of SISCO SV-21 Inventory for the study of academic stress in Peruvian university students - Olivas Ugarte, Lincol Orlando (2021)
This instrumental research was carried out with the objective of analyzing the psychometric evidences of the SISCO SV-21 inventory in university students of Metropolitan Lima. 560 students from public and private universities participated, of both sexes, between 18 and 50 years old. The fit of the model of three correlated factors was corroborated by a confirmatory factor analysis: CFI = .929, TLI = .920, RMSEA = .083 [.078-.088], SRMR = .061. Likewise, reliability was estimated with the omega coefficient (ꞷ>.80) for the three factors: stressors = .90, symptoms = .89, and coping strategies = .89.Therefore, it is concluded that the SISCO SV-21 Inventory gathers validity and reliability evidence for its use in university students in Lima.